2012
DOI: 10.1111/j.1365-2141.2012.09184.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐associated antibodies, cellular immunity and FCGR3a genotype influence the response to rituximab in immune thrombocytopenia

Abstract: SummaryRituximab is widely used in autoimmune diseases including immune thrombocytopenia (ITP), although the mechanism of effect remains unclear. This study describes the effects of rituximab on platelet‐associated antibodies (PA‐APAs), B and T cell counts and clonality ( IGHV and TRG@ gene rearrangements), FCGR3A (FcγRIIIa) and FCGR2A (FcγRIIa) polymorphisms and correlation to anti‐CD40 ligand (CD40L) response. PA‐APA levels fell more frequently in responders (6/8) than in non‐responders (2/10: P = 0·0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 24 publications
1
30
1
Order By: Relevance
“…35 An indirect effect of rituximab on T cells is consistent with other data showing an improvement of T-cell dysregulation after treatment. [36][37][38] A significant proportion of adults with chronic ITP will eventually undergo splenectomy to control their disease. 39,40 Splenectomy itself is associated with a risk of infection that is ;2.6-fold higher than nonsplenectomized ITP patients in the first 90 days after splenectomy, and 1.4-fold higher beyond 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…35 An indirect effect of rituximab on T cells is consistent with other data showing an improvement of T-cell dysregulation after treatment. [36][37][38] A significant proportion of adults with chronic ITP will eventually undergo splenectomy to control their disease. 39,40 Splenectomy itself is associated with a risk of infection that is ;2.6-fold higher than nonsplenectomized ITP patients in the first 90 days after splenectomy, and 1.4-fold higher beyond 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,25 Of interest, the interruption of B-and T-cell interactions by, for example, CD40L antibody, shows a similar therapeutic effect as rituximab in ITP, suggesting that a direct interaction between B cells and T cells is essential for ITP induction. 12 In conclusion, our study suggests that the effectiveness of anti-CD20 therapy is due to induction of a significant CD8 1 T-cell activation/proliferation defect via IL-2 blockade that correlates with their inability to induce thrombocytopenia. This may provide an additional explanation for the therapeutic effects of rituximab in T-cell-mediated ITP.…”
Section: Bdep Therapy Induces Normalization Of Platelet Counts In a Mmentioning
confidence: 61%
“…10,11 Moreover, patients with ITP, whether antiplatelet antibody positive or not, can respond to rituximab and in those antibody-positive patients, their autoantibody titers do not necessarily change. 12 This suggests that anti-CD20 can significantly affect T-cell compartments and this was originally confirmed by Stasi et al showing that rituximab normalizes the observed CD4…”
Section: Introductionmentioning
confidence: 61%
“…Genotyping methodology used for testing FCGR3A variance at nucleotide 559 may result in erroneous interpretation of genotype distribution [10]. The separation of the V/V, V/F and F/F allotypes from each other is technically challenging because of the very close similarities between the FCGR3A and FCGR3B genes [25,33,34]. The high degree of homology between these genes, which are separated by only a single base difference at codon 148 (FCGR3A GAC vs. FCGR3B GAT), may result in a misinterpretation of the genotypes.…”
Section: Discussionmentioning
confidence: 99%